The actor's use of the prosodic elements of speech to express clarity and intent in performance - Munro, Marth (University of Pretoria, 2018)
This study considers the L2 actor’s engagement with L2 text, within a multilingual South African actor-training context, and includes an authoethographic element as I draw from my lived experience as lecturer-director at a university with a multilingual student body. It investigates the challenges that the L2 actor navigates when required to embody and envoice text in a L2 and investigates the prosodic elements of speech as a base for designing creative explorations that could aid the L2 actor and the director in a multilingual context. Prosody is explored, as communicative devise that conveys the meaning and intent of the speaker and utterance, with specific focus on the universal patterns applied to express the primary emotions. This is complimented by consideration of how prosody is implied and applied in the approaches to the actor’s training in acting and theatre-voice. A series of pilot experiments, productions created with L2 actors is discussed through ex-post-facto reflection. This reflection, informed by relevant literature, traces the development of creative explorations that are applied in the study’s formal experiment, a production of Chekhov’s Three Sisters in which the embodied prosody based explorations were used as primary creative and directing strategy. The participants (cast) and researcher (director)’s reflection of the process and elements of the final performance is discussed. The formal experiment concludes that applying creative explorations that are based in pre-linguistic bodyvoice patterns and escalate to include paralinguistic and L1 content could assist the L2 actor in the embodiment of L2 text, towards communicating the character’s intent in performance.